Review of inorganic semiconductor based ultraviolet photodetectors with high internal gain and fast recovery speed. (2016) - Lin, Fanrong; Meng, Leixin
Ultraviolet (UV) photodetectors have important applications in military field, industrial field, environmental field, etc. High performance UV photodetectors characterised as high internal gain (G) and high recovery speed has been studied in decades. In this article, we provide a comprehensive review about recent works on increasing the internal gain of UV photodetectors by improving device configuration, optimising the diameter of the nanowire, applying surface functionalisation and Schottky contact. And the possible solutions to the persistent photoconductivity (PPC) problem which prolongs the recovery time are also discussed.